The Effectiveness Of Health Promotion On The Neglect Of Elderly Through A Transcultural Nursing Approach : Rabab Culture - Amri, Lola Felnanda; Muchtar, Murniati; Novera, Milya (University of Muhammadiyah Semarang, 2023)
Knowledge has a big impact on the formation of a person's behavior. Behavior that is based on knowledge will be lasting compared to behavior that is not based on knowledge. Delivery of knowledge can be done in various ways. One of them is health promotion through traditional culture which is rabab art. Rabab traditional art is a musical instrument from Minangkabau that is made from coconut shell and played by one or more players. The player will sing a rhyme that is called Kaba and it has an educational message such as education about elderly neglectfulness. The objective of this study was to effectiveness of rabab culture on family education about elderly neglectfulness. The study design was a quasi-experimental design with one group pretest post-test. The study was conducted in Gurun Laweh Sub-District, Padang City, West Sumatra Province. The study population was 55 people and number of samples was 48 people. Study results show that most respondents (20 people) were at an early age (58.8%). Before the experiment, people with less knowledge were 11 people (32.4%) and after the experiment, it reduced to 9 people (26.5%). There is a difference in people’s knowledge between before and after the rabab experiment with a P-value of 0.037. It was concluded that there was a need to increase family knowledge about elderly welfare. It is recommended that healthcare workers should provide health education to the community about elderly neglectfulness and future researchers can use different variables and educational media for better results.